A «Frenchman» in Portugal: Bishop D. Hugo of Porto and the transformations of the north-western Iberian Peninsula in the early 12th century - Renzi, Francesco (2023)
The aim of this article is to study Bishop of Porto D. Hugo, a key figure to understand the transformation of Portugal in the 12th century. Probably ailing from France, he was archdeacon in Compostela under Diego Gelmírez and consecrated bishop by Maurice of Braga. D. Hugo dealt with the most important problems of his time: the conflict between the See of Compostela and Braga, the political evolution of the County of Portugal and the relations with the Papacy. The study of D. Hugo reveals a very peculiar image of a medieval bishop: clergyman, politician, writer and tireless traveller.